Catholicism and Society during the Interwar Period in Lithuania - Pruskus, Valdas (Problemos, 2001)
Lithuanian Catholic modernist intellectuals perceived Catholicism and the Church, first of all, as an ecclesiastic institution, entitled to form the attitudes of an individual and the society and their interrelations. However, the terrestrial garment of it at that times did not cause a sympathy to them. According to them, perhaps, the most disadvantage was a formal character of the activities of Catholicism and the Church in Lithuania during the interwar period. They discovered its manifestations in the efforts of the Church of that times to establish religious organizations, trying to involve into their activities representatives of various strata of the society and paying a slight attention to their conscious self-determination and education. Such formal membership, which entitled an individual to call him a believer, as well as the aesthetical-demonstrative manner of being a member of the Church, expressing itself by almost obligatory participation in all mass religious actions (various arrangements), aiming to manifest the Catholic “acting” and solidarity, did not stimulate a conscious and authentic confession of the faith. For this reason, they thought that the Church must refuse too active wardship of believers. Protesting against too active wardship of an individual and a distrust in his ability to make an independent choice and conscious self-determination, which dominated in the practice of the Church of that times, the modernists defended the necessity to revitalize the authentic faith, deeply hidden in a human, to strengthen his religious aspirations and in such way to cherish a spirituality, because no conscious and morally responsible activities are not able without it. It was considered that if the Church would refuse the formalism and more rely on the possibilities of an individual to search independently and authentically the way to the God, it would attract many persons, having doubts of religion and even irreligious ones. In this way it would more widely open itself to the world and because of an acceptance of believers and unbelievers would really become the Mother for everybody. A priest is a main worker of the Church on the Earth, and the image of the Church in the society depends on his actions and the example set by his style of life. Because of this the modernists showed a discretion in a valuation of an involvement of priests and active participation of them in political and economic activities, full of great dangers. Simultaneously, they thought that a priest must be close to an individual and his everyday affairs. But he must pay the most attention to a development of spirituality of believers. So, the priest himself must spiritually grow and overcome his spiritual narrowness: he must stimulate growing of other persons and to grow together with them. The modernists evaluated the social influence of Catholicism and Church of those times according to the scale of high Evangelistic requirements and were not inclined to reconcile themselves with the dominating practice, caused by the specific realities of the life of the Church. Most modernists knew these problems and tried to eliminate them. But they understood that only a good will is not sufficient for a realization of the reforms and that a maturation and the corresponding preparation are necessary for them. This may be implemented by efforts of the Church and the believing society. It is true that the terrestrial garment of Catholicism and the church is important, but not the most important thing. Because of this they did not hurry to initiate the reforms. Irrespectively of this, the thoughts, expressed publicly by modernists, stimulated the heads of the Church to listen to them more attentively and respond to them.
Keywords: social role of Church; catholic modernism; religiosity; religious organizations; Christian faith